ABOUT BLOOD ELOQUENCE (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
The study of blood and blood diseases has led to discoveries of great importance for the survival of mankind. The easy accesibility of a blood sample to research has allowed to leadership advances in basic fields of knowledge as citology, biochemistry, immunology, genetic and molecular biology. The relevance of blood as essential for life as it has been known to humanity thousand of years before blood circulation. When a big volume of blood was lost life was extinguised. The aim of this work is to review the deep impact of blood concept on history of thought, through language, poetry, literature, geography, policy and science.
Keywords: blood; language; literature, policy; science